Assuming that

**k**and**c**are just constants, the equation is separable, divide both ...subject, divide both sides by -1 and raise both sides to the base of e:**c**- y = e^(-kx) * e^-**C**As e^-**C**represents a constant...3 Answers · Science & Mathematics · 17/08/2013

f(2) = 2² + k (2) + c = 0 f(-3) = -3² + k (-3) + c = 35 Drop the functions on the left and multiply...4 - 12 + 8 = 0 9 + 18 + 8 = 35 -8 + 8 = 0 27 + 8 = 35 0 = 0 35 = 35 This checks. k = -6 and c = 8

3 Answers · Science & Mathematics · 15/05/2014

**C**=**k**/ (m(1 -**k**)) cross multiply Cm(1 -**k**) =**k**distribute LHS Cm - Cmk =**k**add Cmk to both sides Cm =**k**+ Cmk factor Cm =**k**(1 + Cm) divide both sides by (1...3 Answers · Science & Mathematics · 26/08/2008

Do you mean y = asin[

**k**(x -**c**)] + d? y = asin[**k**(x -**c**)] + d Subtract both sides by d: y...d)/a)/**k**Finally, add both sides by**c**: x = arcsin((y - d)/a)/**k**+**c**I hope this helps!1 Answers · Science & Mathematics · 25/02/2011

See binomial equation [1 + x]^n = C (n,0)+ x* C (n,1) +(x^2)* C (n,2)+ (x^3)* C (n,3) ... + [x^n-1...(n,1)+ (2*x)* C (n,2) + (3x^2)* C (n,3)+ ... + (n-1)*[x^n-2]⋅ C (n,n-1) + n*[x^n-1]* C (n,n) put x = 1, you will see that right part is...

3 Answers · Science & Mathematics · 28/10/2015

...black is given by the well-known hyper-geometric formula: P(

**k**) =**C**[M,**k**] ***C**[(N-M),(n-**k**)] /**C**[N,n], /numerator...1 Answers · Science & Mathematics · 05/09/2007

... in the formula: since

**k**= n - (n-**k**), we have:**C**(n,**k**) = n! / (**k**! (n-**k**)! )**C**(n, n-**k**) = n! / ((n-**k**)! (n - (n-**k**))! = n! / ( (n-**k**)!**k**! )1 Answers · Science & Mathematics · 14/03/2012

Since the series includes the term (x- c )^ k we know the power series expresses a function of x "centered at...all over |a_ k (x- c )^ k | is less than 1. So... lim k »∞ | a_( k +1)(x- c )^( k +1) / [a_ k (x- c )^ k ] | < 1 Since (x- c )^( k +1)/(x- c )^ k can...

1 Answers · Science & Mathematics · 06/12/2012

...1 Now put x = 1 and you will get ......................n n*(2)^(n - 1) = ∑ k * C (n, k ) ................... k =1

3 Answers · Science & Mathematics · 24/11/2009

Use the Quotient Rule. = [1-e^(-alpha(u)] [

**k**+(**c**)(lamba)] - [**k**+(**c**)(lamda)(u)) (-e^(-alpha(u)) (-alpha)] / (1-e^(-alpha)(u)]^2 Note...1 Answers · Science & Mathematics · 27/03/2008